Effectiveness of Some Relaxation Exercises Use by Nurse in Assessment of Vital Signs (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: The objective of this study was to assess the short term effect of relaxation exercise on vitalsigns measured at baseline.Method: A quasi-experimental design with pre and post-intervention with a group control method. Sixtysubjects, divided to study and coronal group measurement of vital signs (Temperature, pulse, respiration andblood pressure) done by researchers, by using a calibrated sphygmomanometer, mercury thermometer, anddone of four relaxation exercises include (deep breathing, leg relaxation exercise, arm relaxation exercise,and face muscles relaxation exercise).Results: The findings of research appear there is a significant difference between the study and controlsample in vital signs after applied relaxation techniques, and This table reveals the statistical significanceand high significance between study and control study for the physical parameter (vital signs) after appliedthe relaxation technique.Conclusions: The currents study concludes, some relaxation exercises such as (deep breathing, leg relaxationexercise, arm relaxation exercise, and face muscle relaxation exercise) after application for a study group,make a slight alteration in vital signs. And there is no significant association among the control group. Theauthors recommend the training of the office employees about some relaxation exercises.
Keywords: Effect, Nurse, Relaxation Exercise, Vital Signs, Measurement.